Rancangan Intervensi Rancangan Intervensi bagi Peserta Didik dengan Hambatan Intelektual - Lase, Vasas Elkasih; Shidqi, Teguh Shulha; Rahmatrisilvia, Rahmatrisilvia (JPI (Jurnal Pendidikan Inklusi), 2025)
Abstract Students with intellectual disabilities face challenges in cognitive, social, and adaptive aspects that have a significant impact on the learning process. The urgency of individually designed educational interventions is important to support their optimal development. The purpose of this study was to design and analyze the effectiveness of IEP-based individual education programs (IEP) to improve basic and social knowledge of students with intellectual disabilities. Using a qualitative case study approach, data were obtained through observation, in-depth interviews, and documentation which were then analyzed using Miles & Huberman data reduction techniques. The results showed that the application of strategies such as task analysis, positive reinforcement, and parental involvement can consistently improve students' reading skills, independence in daily activities, and social interactions. This study provides theoretical contributions to strengthening behavioral approaches and ZPD in special education, providing practical impacts on teachers, schools, and intervention programs that are integrated with political decision making. Further research is recommended to expand the scope of subjects and duration of intervention in order to obtain more comprehensive results. Keywords: educational intervention, intellectual disability, IEP, inclusive education.